2008
DOI: 10.1128/jvi.02164-07
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Therapy during Primary Simian Immunodeficiency Virus Infection Fails To Prevent Acute Loss of CD4 + T Cells in Gut Mucosa but Enhances Their Rapid Restoration through Central Memory T Cells

Abstract: Gut-associated lymphoid tissue (GALT) is an early target of human immunodeficiency virus (HIV) and simian immunodeficiency virus (SIV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
78
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 75 publications
7
78
1
Order By: Relevance
“…in untreated animals. In line with our findings, Verhoeven et al (31), using a similar ART regimen (30 mg/kg of body weight) that was initiated at day 7 p.i., reported a significant decline in plasma viral loads at 2 weeks p.i. in treated animals compared to those in untreated animals.…”
supporting
confidence: 79%
“…in untreated animals. In line with our findings, Verhoeven et al (31), using a similar ART regimen (30 mg/kg of body weight) that was initiated at day 7 p.i., reported a significant decline in plasma viral loads at 2 weeks p.i. in treated animals compared to those in untreated animals.…”
supporting
confidence: 79%
“…Such severe CD4 ϩ T-cell impairment has been shown to preferentially involve gut-residing memory-activated CD4 ϩ CCR5 ϩ T cells, reflecting the well-known prevalence of CCR5-tropic viruses in the early phases of infection. Almost concomitantly, Veazey et al and Kewenig et al showed that more than 70% of intestinal CD4 ϩ cells were depleted as early as 21 days post-SIVmac239 infection (72,73), and several subsequent studies then confirmed these findings and shed further light onto the mechanistic pathways underlying CD4 ϩ T-cell depletion (34,(74)(75)(76). Among those studies, Mattapallil et al were able to demonstrate the presence of SIV DNA in up to 60% of intestinal CD4 ϩ T cells as early as 10 days after experimental SIVmac251 infection, therefore emphasizing the role of direct virus-mediated killing of CD4 ϩ T cells as a mechanism causing the observed depletion (70).…”
Section: Pathogenesis Of Hiv/siv-associated Microbial Translocationmentioning
confidence: 57%
“…During chronic HIV infection, several studies have shown that maintenance of EM numbers is dependent on the preservation of CM cells for their homeostasis and that this CM-dependent EM production progressively declines during chronic infection (25,33). The frequency of CD4 CM cells in GALT was found to be associated with better mucosal CD4 T cell restoration (9,44,48). Despite replenishing of the EM pool by CM cells, the frequency of CD4 cells remains low at the mucosal sites during chronic HIV infection compared to uninfected individuals (9,44).…”
mentioning
confidence: 99%